Case Report: Lenvatinib for the treatment of recurrent hepatocellular carcinoma in people living with HIV: a report of two cases - Morsica, Giulia; Bertoni, Costanza; Hasson, Hamid; Messina, Emanuela; Uberti Foppa, Caterina (Frontiers in Oncology, 2023)
The use and choice of the best systemic treatment is gaining increasing in interest in people living with HIV (PLWH) because HCC represents an increasing cause of morbidity and mortality in this setting and most HCC are diagnosed in advanced stage. Ten years ago, the multi-kinase inhibitor lenvatinib was approved in first-line setting. However, to date, no data on the efficacy and tolerability of lenvatinib in PLWH from clinical trials and real-life studies are available. Case 1 was a gentleman, with hepatitis B virus-related cirrhosis who underwent orthotopic liver transplantation (OLT) for HCC and developed peritoneal metastasis several years later. Lenvatinib treatment was selected at HCC recurrence. This participant maintained undetectable HIV-viremia and a relatively preserved immune status during 6 months of systemic treatment with lenvatinib. After 6 months, he discontinued lenvatinib for progression of the disease (growing of peritoneal metastasis) and uncontrolled hypertension. Case 2 was a gentleman with hepatitis C-genotype 1a-related cirrhosis who experienced unresectable recurrences after radiofrequency thermo ablation (RFTA) of the tumour. At the first recurrence HCC was treated with 6 cycles of trans-catheter arterial chemoembolization (TACE), at second recurrence the participant underwent trans-catheter arterial radio embolization (TARE) and at third recurrence he received lenvatinib. A week after start of lenvatinib the participant had liver decompensation and discontinued therapy. The presently reported cases showed low tolerability of systemic therapy with lenvatinib in PLWH. Cumulative data are necessary to define the position of lenvatinib in this setting.